2005
DOI: 10.1002/em.20100
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of inorganic lead salts and disturbance of microtubule function

Abstract: Lead compounds are known genotoxicants, principally affecting the integrity of chromosomes. Lead chloride and lead acetate induced concentration-dependent increases in micronucleus frequency in V79 cells, starting at 1.1 microM lead chloride and 0.05 microM lead acetate. The difference between the lead salts, which was expected based on their relative abilities to form complex acetato-cations, was confirmed in an independent experiment. CREST analyses of the micronuclei verified that lead chloride and acetate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…Lead acts directly by inhibiting neutrophil chemotactic activity both in vivo and in vitro (Governa et al 1987(Governa et al , 1988. Furthermore, it can interfere with their cell membrane fluidity in vivo (Valentino et al 1982) and with their cytoplasmic microtubular network in vitro (Bonacker et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Lead acts directly by inhibiting neutrophil chemotactic activity both in vivo and in vitro (Governa et al 1987(Governa et al , 1988. Furthermore, it can interfere with their cell membrane fluidity in vivo (Valentino et al 1982) and with their cytoplasmic microtubular network in vitro (Bonacker et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is possible that lead ions could contribute to lead chromate-induced centrosome amplification. Studies show that lead ions do enter the cell after lead chromate exposure (17), and a recent study by Bonacker et al showed that soluble lead ions disrupt microtubule function and formation (34). However, lead's effect on centrosome function is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…According to Johnson (1998) lead and its compounds are capable of interfering with the spindle apparatus of dividing cells thus leading to genotoxicity. Bonacker et al (2005) thought that the micronuclei induced by lead ions are most often associated with processes involving reactive oxygen generated by redox shuttling. Oxidative stress as a result of metal toxicity is also described to play a major role in DNA-damage induction (Halliwel, 1990).…”
Section: Micronucleus Test and Mechanism Of Lead-induced Genotoxicitymentioning
confidence: 99%